2000
DOI: 10.1038/sj.bjp.0703232
|View full text |Cite
|
Sign up to set email alerts
|

Selective cyclo‐oxygenase‐2 inhibition with celecoxib elevates blood pressure and promotes leukocyte adherence

Abstract: 1 Selective inhibitors of cyclo-oxygenase-2 have been shown to be e ective anti-in¯ammatory drugs with reduced gastrointestinal toxicity relative to conventional nonsteroidal anti-in¯ammatory drugs (NSAIDs). In the present study, we examined the possibility that selective COX-2 inhibition, by blocking prostacyclin synthesis, would increase blood pressure and cause leukocyte adherence and platelet aggregation. 2 Normal rats and rats with hypertension induced by chronic administration of N o -nitro-Larginine met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
81
1
3

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(92 citation statements)
references
References 30 publications
7
81
1
3
Order By: Relevance
“…The physiological consequences of eicosanoid metabolite production by the COX-2 enzyme are tissue and cellspecific. In vascular systems, COX-2-dependent production of prostacyclin can affect platelet coagulation [19][20][21] and leukocyte adhesion [22,23]. COX-2 activation in endothelial cells and vascular smooth muscle cells plays a vital role in the development and stability of atherosclerotic plaque.…”
Section: Introductionmentioning
confidence: 99%
“…The physiological consequences of eicosanoid metabolite production by the COX-2 enzyme are tissue and cellspecific. In vascular systems, COX-2-dependent production of prostacyclin can affect platelet coagulation [19][20][21] and leukocyte adhesion [22,23]. COX-2 activation in endothelial cells and vascular smooth muscle cells plays a vital role in the development and stability of atherosclerotic plaque.…”
Section: Introductionmentioning
confidence: 99%
“…These observations hint at potential additional counterregulatory roles for the enzyme and PGE 2 that may become evident with further investigations of the kinetics of complex inflammatory responses, such as delayed-type hypersensitivity, which require prominent contributions from the adaptive immune system for resolution (27). In several other models of inflammation, pharmacologic inhibition of COX-2 decreases PGE 2 , but not leukocyte infiltration (29,32 a striking protection from collageninduced arthritis, with diminished pannus formation, preservation of proteoglycan at articular surfaces, and less bony erosions. Antibodies against type II collagen were detected in both control and the mPGES1-deficient mice, but the titers were decreased in mPGES1-deficient animals.…”
mentioning
confidence: 99%
“…Some studies have shown an increase in blood pressure for both drugs celecoxib and rofecoxib. 18,19 We did not find any other studies about the influence of nabumetone on blood pressure.…”
Section: Discussionmentioning
confidence: 75%